Biochemical Characteristics of the Formulation and Preparation of Telang Flower Kombucha Jelly as an Antioxidant, Food and Pharmaceutical Biotechnology Products - Ahmad Saddam Hussein; Rezaldi, Firman; Elok Zubaidah; Wijayanti Wijayanti; M. Fariz Fadillah; Muhammad Faizhal Fathurrohim; Sukardi Sugeng Rahmad; Fitria Eka Resti Wijayanti; Dyah Rohma Wati; Andri Tri Cahyono (Journal of Health and Nutrition Research, 2024)
One of the functional food preparations which is soft formulated and made from hydrocolloid ingredients which include agar, gum, carrageenan, pectin and gelatin is jelly candy. In the formulation and preparation of jelly candy, which aims to increase its functional value, in this research, bioactive compounds are added which function to improve the health aspects of consuming it. In this research, jelly candy is made from butterfly pea flower kombucha because it contains organic acid compounds, polyphenols, vitamins, amino acids, so it is good for body health. Kombucha is made from butterfly pea flowers because previous research results have been proven to be antibacterial, antifungal, antioxidant, antifungal, anticholesterol and anticancer. Telang flowers contain secondary metabolite compounds which are divided into alkaloids, flavonoids, saponins, terpenoids, acetogenin which are cytotoxic for the growth of cancer cells and are efficacious as a source of antioxidants. The jelly candy product produced has been tested to meet the SNI 3547.2-2008 quality standard where the water content produced is 16.25%. ash content 0.35%. And pH 4.57. Jelly candy preparations made from the active ingredient telang flower kombucha which are designed as food and pharmaceutical biotechnology products have biochemical characteristics in warding off free radicals which refer to an IC50 value of 62.848 μg/mL